Meta-analysis of recurrent laryngeal nerve injury in thyroid surgery with or without intraoperative nerve monitoring - RULLI, F. (Pacini Editore SpA, 2014)
Intraoperative nerve monitoring (IONM) aimed at reducing the injuries of recurrent laryngeal nerve during thyroidectomy is controversial. We conducted a meta-analysis to assess the incidence of nerve injuries with or without IONM. Studies published from January 1994 to February 2012 in English language on humans were identified. Heterogeneity of studies was checked by the Higgins test. Summary estimates of predictive values of injury were made using the Mantel-Haenszel test based on the fixed-effects model. Publication bias was assessed by a funnel plot and Egger's method. Eight articles were selected accounting a total of 5257 nerves at risk. IONM revealed a significant impact in preventing transient injuries (positive predictive value = 5% [95% CI: 2-8], negative = 96% [95% CI: 91-100], relative risk = 0.73 [95% CI: 0.54-0.98], p = 0.035), whereas they failed to demonstrate effect on permanent injuries (positive predictive value = 2% [95% CI: 0.6-3.8], negative 99% [95% CI: 97-100], relative risk = 0.73 [95% CI: 0.44-1.23], p = 0.235). This meta-analysis demonstrated the merit of IONM in preventing transient injury during thyroidectomy. No advantage was found in permanent injuries.